Analisis Kesesuaian Lahan Permukiman di Kecamatan Pasaman Menggunakan Sistem Informasi Geografis - Khairunnisa, Khairunnisa; Ttiyatno, Ttiyatno (Al-DYAS, 2024)
Settlements are part of the living environment that functions as a residential environment. The conditions of a settlement greatly influence the survival of living creatures in that settlement. Spatial planning for a residential location needs to be based on various considerations to make it more appropriate and efficient, mSo there needs to be efforts to adapt the land, Therefore, the aim of this research is to analyze the level of suitability of residential land in Pasaman District using the method matching and spatial analysis, namely geographic information systems. Settlement land suitability analysis for Pasaman District is divided into 3 classes, namely suitability classes S2, S3, and N. For class S2, which is the land suitability class suitable for settlements, has an area of 16,105 Ha (37%), class S3 or suitable marginal with an area of 14,188.21 Ha (32%), and class N or not suitable with an area of 13,807.26 Ha (31%). The dominant inhibiting or limiting factors for land suitability classes in Pasaman District are slopes, river borders, road accessibility and flood vulnerability.